HNK-1 in Morphological Study of Development of the Cardiac Conduction System in Selected Groups of Sauropsida - Kvasilova, Alena; Gregorovicova, Martina; Kundrat, Martin; Sedmera, David (Anatomical record (Hoboken, N.J., 2019)
Human natural killer (HNK)-1 antibody is an established marker of developing cardiac conduction system (CCS) in birds and mammals. In our search for the evolutionary origin of the CCS, we tested this antibody in a variety of sauropsid species (Crocodylus niloticus, Varanus indicus, Pogona vitticeps, Pantherophis guttatus, Eublepharis macularius, Gallus gallus, and Coturnix japonica). Hearts of different species were collected at various stages of embryonic development and studied to map immunoreactivity in cardiac tissues. We performed detection on alternating serial paraffin sections using immunohistochemistry for smooth muscle actin or sarcomeric actin as myocardial markers, and HNK-1 to visualize overall staining pattern and then positivity in specific myocyte populations. We observed HNK-1 expression of various intensity distributed in the extracellular matrix and mesenchymal cell surface of cardiac cushions in most of the examined hearts. Strong staining was found in the cardiac nerve fibers and ganglia in all species. The myocardium of the sinus venosus and the atrioventricular canal exhibited transitory patterns of expression. In the Pogona and Crocodylus hearts, as well as in the Gallus and Coturnix ones, additional expression was detected in a subset of myocytes of the (inter)ventricular septum. These results support the use of HNK-1 as a conserved marker of the CCS and suggest that there is a rudimentary CCS present in developing reptilian hearts. Anat Rec, 302:69-82, 2019. © 2018 Wiley Periodicals, Inc.
Keywords: heart; Coturnix; počítačové zpracování obrazu; imunohistochemie; monoklonální protilátky; Leu 7; Antibodies, Monoclonal; CD 57; převodní systém srdeční; Immunohistochemistry; immunohistochemistry; myokard; zvířata; biologické markery; Heart Conduction System; Myocardium; Image Processing, Computer-Assisted; reptile; antigeny CD57; Biomarkers; CD57 Antigens; Animals